Hybrid magnetic graphitic nanocomposites for catalytic wet peroxide oxidation applications - Rui S. Ribeiro (2017)
Fe3O4, with a lattice parameter a = 8.357 A and average particle size of 12.5 +/- 3.6 nm, was successfully encapsulated within a graphitic structure by a hierarchical co-assembly approach, followed by thermal annealing. The resulting material was denoted as MGNC-magnetic graphitic nanocomposite. MGNC possesses average core size of 109 +/- 35 nm (mainly composed by agglomerates of magnetic nanoparticles), stability up to 400 degrees C under oxidizing atmosphere, a micro-mesoporous structure with a fairly developed specific surface area (S-BET = 330 m(2) g(-1)) and neutral character (pH(PZC) = 7.1). Catalytic wet peroxide oxidation (CWPO) experiments performed with a 4-nitrophenol (4-NP)/Fe3O4 mass ratio fixed at 36.6, allowed to achieve high efficiency of catalyst usage throughout the wide range of 4-NP concentration considered (200 mg L-1-5 g L-1). The inclusion of Fe3O4 nanoparticles in a graphitic structure during the synthesis of MGNC was found to (i) enhance the catalytic activity in CWPO when compared to Fe3O4, due to increased adsorptive interactions between the surface of the catalyst and the pollutant molecules, while (ii) strongly limiting the leaching of Fe species from Fe3O4 to the treated water, due to the confinement effect caused by the carbon shell. As a result of these effects, unprecedented pollutant mass removals were obtained ranging from 5000 mg(-1) h(-1), when the CWPO process is performed with [4-NP](o) = 200 mg L-1 at pH = 3, to 1250 mgg(-1) h(-1), when [4-NP](o) = 5 g L-1. High efficiency of H2O2 consumption is obtained when MGNC is applied in the CWPO of 4 -NP solutions at pH = 3, with TOC removals per unit of H2O2 decomposed (n(H2O2)) in the range 64-100%. In addition, the MGNC catalyst is also active at pH = 6; in this case a pollutant mass removal of 2090 mg g(-1) h(-1) was obtained. Although MGNC partially deactivates through successive reusability cycles, the pollutant mass removal obtained at the end of the fourth cycle is still very high when 200 mg L-1 4-NP solutions are considered (4808 mg g(-1) h(-1), representing only a ca. 4% decrease when compared to the first cycle). A higher deactivation of the MGNC catalyst is observed when 5 gL(-1) 4-NP solutions are employed. Nevertheless, the pollutant mass removal obtained at the end of the third cycle is still high (551 mgg(-1) h(-1)).